The Efficacy of Combination Therapy Involving Excision Followed by Intralesional 5-Fluorouracil and Betamethasone, and Radiotherapy in the Treatment of Keloids: A Randomized Controlled Trial - Li Y; Zhang D; Hang B; Wang H (Dove Medical Press, 2022)
Yazhuo Li, Dewu Zhang, Bing Hang, Hao Wang Department of Dermatology, the Second Affiliated Hospital of Xi'an Jiaotong University (Xibei Hospital), Xi'an, People's Republic of ChinaCorrespondence: Hao Wang, Department of Dermatology, the Second Affiliated Hospital of Xi'an Jiaotong University (Xibei Hospital), No. 157, West 5th Road, Xi'an, Shaanxi Province, 710004, People's Republic of China, Tel +86 182 9183 9156, Email wanghaonxyc@xjtu.edu.cnBackground: Combined therapy for keloids is currently recommended. Surgery is one of the main options, but the measures to prevent recurrence after excision are still being explored.Objective: The randomized controlled study aimed at evaluating the efficacy of excision followed by intralesional low concentrations of 5-fluorouracil (5-FU)(12.5 mg/mL) and betamethasone.Methods: Sixty patients were randomly assigned to three groups. Patients in group A had excision followed by 5-FU and betamethasone intralesional injections, group B had 5-FU and betamethasone intralesional injections, and group C had excision followed by radiotherapy. Efficacy parameters were assessed from 8 to 12 months, including improvement on the Vancouver Scar Scale (VSS) and the Patient and Observer Scar Scale (POSAS), as well as side effects and recurrence. Trial registration number: ChiCTR2100046025.Results: After 4 months' treatment, the improvement of the VSS and POSAS scores in group A was not different from that in group C (P > 0.05) but was superior to that in group B (P < 0.05); the pain and pruritus of the three groups were relieved more than 50%. After 8 to 12 months' follow-up, there was no statistical difference in the incidence of side effects and recurrence among the groups (P > 0.05).Conclusion: Excision followed by intralesional low concentrations of 5-FU (12.5mg/mL) with betamethasone is a safe and sustainable treatment for keloid, with no significant difference from excision followed by radiotherapy.Keywords: keloid, excision, 5-fluorouracil, betamethasone, radiotherapy